How humans judge machines - Hidalgo, César A. 1979-; Orghian, Diana ca. 20. Jh; Albo-Canals, Jordi ca. 20. Jh; Almeida, Filipa de ca. 20. Jh; Martin, Natalia (The MIT Press, 2021)
"80 experimental scenarios help us understand how humans judge AIs as opposed to other humans in the same situation"--
Literaturangaben
Keywords: Künstliche Intelligenz; Mensch-Maschine-Kommunikation; Ethik; Artificial intelligence / Moral and ethical aspects